2012
DOI: 10.1080/15313204.2012.729179
|View full text |Cite
|
Sign up to set email alerts
|

Race and White Transracially Adoptive Mothers

Abstract: Eight transracially adoptive mothers of Asian-born children were interviewed about their perceptions of their role in the racial socialization of their children. The findings suggest a possible relationship between these mothers' choices in racial socialization practices with their families and their views on race and racial differences. Findings are discussed in relation to future research and practice with transracially adoptive parents and their families.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
9
0

Year Published

2015
2015
2020
2020

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 12 publications
(9 citation statements)
references
References 25 publications
0
9
0
Order By: Relevance
“…Sometimes, White parents themselves are treated differently as they are violating racial norms by parenting a child of color (Rauktis et al, ). Indeed, as White parents are able to experience and empathize with people of color and integrate their experiences into their own understanding of race, the more they are willing and motivated to engage in ethnic–racial socialization (Crolley‐Simic & Vonk, ). Despite witnessing mistreatment and discrimination, many White parents are unprepared to cope with and prepare their youth for discrimination.…”
Section: Ethnic–racial Socialization In Family and Neighborhood Contextsmentioning
confidence: 99%
“…Sometimes, White parents themselves are treated differently as they are violating racial norms by parenting a child of color (Rauktis et al, ). Indeed, as White parents are able to experience and empathize with people of color and integrate their experiences into their own understanding of race, the more they are willing and motivated to engage in ethnic–racial socialization (Crolley‐Simic & Vonk, ). Despite witnessing mistreatment and discrimination, many White parents are unprepared to cope with and prepare their youth for discrimination.…”
Section: Ethnic–racial Socialization In Family and Neighborhood Contextsmentioning
confidence: 99%
“…In addition, research suggests a relationship between racial awareness and socialization practices. For example, Crolley-Simic and Vonk (2012) found that ''mothers' decisions and choices about how to racially socialize their children appeared for the most part to be congruent with their racial views'' (p. 209). The more a mother integrated the perspectives of persons of color into her racial views, the more she included activities outside the culture in the racial socialization of her child.…”
Section: Cultural and Racial Socializationmentioning
confidence: 99%
“…These items informed that the items are specific individual practices. In addition, empirical literature related to racial socialization practices in transracial adoption resulted in the addition of 11 items (Berbery & O’Brien, 2011; Crolley-Simic & Vonk, 2008, 2011, 2012; Huh & Reid, 2000; Johnston et al, 2007; R. M. Lee et al, 2006; McGinnis et al, 2009; Rojewski, 2005; Song & Lee, 2009; Tessler, Gaumache, & Liu, 1999; Thomas & Tessler, 2007; Vashchenko et al, 2011; Vonk, Yun, Park, & Massatti, 2007; Yoon, 2004).…”
Section: Development Of the Taps-rmentioning
confidence: 99%
See 1 more Smart Citation
“…While cultural socialization practices appear to occur to at least some degree in the majority of transracial adoptive families, racial socialization practices may not be as prevalent (Berbery & O'Brien, 2011). This may be related to discomfort and lack of knowledge on the part of White parents who have had little experience with bias, prejudice, or discrimination (Crolley-Simic & Vonk, 2012;Vonk, Yun, Park, & Massatti, 2007). Parents may be encouraged to increase racial socialization practices by including them with cultural socialization, for example, by using birth culture experiences as an avenue for conversations with their children that reflect the stories or perspectives of people of color (Crolley-Simic & Vonk, 2008;Mohanty & Newhill, 2011).…”
Section: Racial Socialization Practicesmentioning
confidence: 99%